(untitled) (The Pretoria Student Law Review, 2021)
This article attempts to analyse a single aspect of the #FeesMustFall movement, namely, university language policies. The research problem is defined as an unjustifiable underdevelopment of indigenous African languages as mediums of instruction at institutions of higher education. The research problem is situated with defective university language policies. Firstly, most current language policies detract from a national framework on the advancement of indigenous African languages. Secondly, most current university language policies have no clear implementation plan and the advancement of their specified African indigenous language(s) remains unrealised. This underdevelopment of indigenous African languages can also be attributed to the ‘Anglicisation’ of the higher education sphere. Finally, this paper utilises and builds on the Language Policy for Higher Education and a 2005 Ministerial Committee Report on the development of indigenous African languages in universities, ultimately proposing implementable policy considerations in (re)addressing the underdevelopment of indigenous African languages as mediums of instruction across all public institutions of higher education.